HUBUNGAN SOSIAL ANTARA PEDAGANG PENGUMPUL DENGAN PERAJIN BATU BATA DI RW 27 KELURAHAN SAIL KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Rudi Royman Butar-Butar; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This thesis is submitted in order to qualify holds a Bachelor of Sociology. With the title “social relationship beetween the collector with crafters bricks in RW 27 sail village tenayan raya district pekanbaru”. The issue discussed in the thesis this is social relationship between crafters bricks with a foraging tenayan raya Pekanbaru. respondents from this research is 60 crafters bricks and 3 of the collector, each a collector has about 14 crafters bricks. The samples used in this study is a proportional random sampling. This technique a sampling of each, the population by taking into account the size of sub-sub the population. The method used is the method of research quantitative descriptive because this method more emphasis on aspects of the objective of social phenomena. Instruments screening data used is an observation, a questionnaire, and documents. The use of exchange, the analysis of social relations that occurs according to its cost and reward this is one of the hallmark of the theory of exchange. The results in general, the writer can say that the high level of dependence between crafters bricks with a collector because it is based both have interest. Conflict is intended that artisans brick up in terms of marketing products if over the production of and assintance in meeting the necessities of life be review in terms of lending money to a collector. As a collector benefit from artisans of the production of bricks only in selling him even though the price of the collective agreement but sometimes there is also the price of overidden by a collector, in addiction there are of the loan in given by a compiler to artisans and traders the benefit of lending in giving it to artisans.Keyword : artisans, social realtionship, dependency